2012
DOI: 10.1177/1933719111430998
|View full text |Cite
|
Sign up to set email alerts
|

Statins Inhibit Monocyte Chemotactic Protein 1 Expression in Endometriosis

Abstract: Statins are potent inhibitors of the endogenous mevalonate pathway. Besides inhibiting cholesterol biosynthesis, statins may also demonstrate anti-inflammatory properties. Inflammation is implicated in the attachment and invasion of endometrial cells to the peritoneal surface and growth of ectopic endometrium by inducing proliferation and angiogenesis. In this study, the effect of statins on monocyte chemotactic protein 1 (MCP-1) expression in endometriotic implants in nude mouse model and in cultured endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
(83 reference statements)
0
32
0
2
Order By: Relevance
“…The revealed data based on experimental research show that statins have the potential to both inhibit and promote neovascularization (Asai et al, 2012;Cakmak et al, 2012;Hu et al, 2008;Massaro et al, 2010). It was proposed that statins have a proangiogenic effect at low concentrations (nanomolar), whereas higher concentrations (micromolar) decrease angiogenesis (Urbich et al, 2002;Weis et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…The revealed data based on experimental research show that statins have the potential to both inhibit and promote neovascularization (Asai et al, 2012;Cakmak et al, 2012;Hu et al, 2008;Massaro et al, 2010). It was proposed that statins have a proangiogenic effect at low concentrations (nanomolar), whereas higher concentrations (micromolar) decrease angiogenesis (Urbich et al, 2002;Weis et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…They demonstrated a potent inhibitory effect of simvastatin on the development of endometriosis and on matrix metalloproteinase-3 (MMP-3) [ 10 ]. Cakmak et al investigated the effects of simvastatin (5 and 25 mg/kg/d for 10 d) in a nude mouse model of endometriosis, and observed a significant decrease in MCP-1 production [ 27 ]. However, no studies have reported the effect of simvastatin on endometriosis in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory properties of simvastatin and mevastatin have been demonstrated by both in vitro culture of endometrial cells and endometriosis induced in mice (31). In both models, monocyte chemotactic protein-1 (MCP-1) expression was inhibited by these drugs in a dose-dependent fashion.…”
Section: Statinsmentioning
confidence: 98%